Effect of Terminalia arjuna (add-on medication) on Cardiac Function In Patients of Coronary Artery Disease – A Randomized Controlled Clinical Study - Kuchewar, Vaishali; Acharya, Sourya (International Journal of Psychosocial Rehabilitation, 2020)
Background - Coronary artery disease (CAD) is a major cause of death all over globe.Its incidence is rapidly increasing in developing countries also. Despite significant diagnostic and interventional advancement in cardiovascular area, still it is the most common cause of morbidity and mortality. So there is need of integrated approach & to search a medicine which is cardio protective & Rejuvenating. Terminalia arjuna is described as Hridya(Cardio protective). Objective -This study is planned with the objective to evaluate the effect of Terminalia arjuna on Cardiac function in CAD patients. This drug will be given with the drugs prescribed by the cardiologist as add-on medication. Methodology - It is parallel group, exploratory hospital based study. The patients of Coronary artery disease of age group 40 to 70 years will be screened as per inclusion/exclusion criteria and randomly divided into two groups. One group will be received standard conventional treatment and the other group will be on standard conventional treatment with stem bark of Terminalia arjuna(capsule form). The treatment period will be of 90 days. Patients will be closely followed up throughout the trial period every week for first four weeks and then fortnightly for another eight weeks. Primary outcomes include evaluation of effect of Terminalia arjuna on cardiac function with the help of ejection fraction and 6MWT. Secondary outcomes involve evaluation of vascular inflammatory marker (hsCRP) and lipid profile. Ethics approval was obtained from IEC,DMIMS (DMIMS(DU)/IEC/Aug-2019/8309). The conclusion will be drawn from the results and will be published in peer reviewed journal.